0192 Implementing Themes From Serious Incidents Into Simulation Training For Junior Doctors. (1st November 2014) - Peerally, Mohammad Farhad; Fores, Mark; Powell, Robert; Durbridge, Moira; Carr, Sue
Abstract : Background: A tenth of patients admitted to hospitals may be subjected to avoidable harm. 1 Junior doctors are very likely to be involved in such incidents. 2, 3 In the University Hospitals of Leicester, each reported serious incident (SI) undergoes a root cause analysis and an action plan is implemented for each SI. Tackling each SI independently is an approach that does not address recurrent errors across incidents. Simulation offers a platform to implement the educational principle of "learning from mistakes" in a safe environment. This study describes the implementation of a simulation programme based on recurring themes across SIs in a large NHS trust. Methodology: SI reports involving junior doctors over a two year period were qualitatively analysed to identify recurring themes across incidents. These themes were used to design high-fidelity simulation scenarios which were integrated into a training programme for postgraduate medical trainees across numerous specialties. Time was allocated for debriefing using the principles of "advocacy with enquiry". The simulation was complemented by a reflective exercise using a written narrative of a real serious incident. Trainees then filled an online evaluation questionnaire. Results: Recurring themes included "poor prescribing practice", "failure of clinical reasoning", "poor record keeping". 19 trainees underwent a one day fully immersive simulation course in groups of three to six, participating in three scenarios. 100% of trainees felt that the scenarios were realistic, 90% felt that this educational approach could reduce the number of SIs, 100% felt that the group discussion on a real SI allowed them to reflect on ways to reduce errors in clinical practice. Potential impact: This model demonstrates how simulation can be used as a potent educational tool to promote active learning from important themes leading to SIs. The next step involves performing a departmental qualitative analysis followed by multi-disciplinary departmental simulation training. Correction notice: MDW was removed from this author list as she was involved in the investigative stage and not involved in the interventional stage, which was what this abstract is mostly about. References: National Audit Office. Patient Safety. 2009: HC 151-I Berk WA, Welch RD, Levy PD, et al . The effect of clinical experience on the error rate of emergency physicians. Ann Emerg Med 2008;52(5):497–501